Evaluation of methods for the rapid identification of Neisseria gonorrhoeae in a routine clinical laboratory. - Pollock, H M (1976)
Of 78 isolates of Neisseria gonorrhoeae, 21 failed to grow and produce acid in unsupplemented cystine-Trypticase agar (CTA); whereas positive reactions were obtained by using serum-supplemented CTA and fluorescent antibody (FA). An additional 290 strains of Neisseria were evaluated by FA and by a rapid carbohydrate degradation technique (RF). There was agreement between the two methods 92% of the time on the initial trial and 99% of the time with repeats on discrepancies. The RF and FA tests provided rapid and reliable identification of N. gonorrhoeae, alleviating the problems of CTA due to lack of growth and need for overnight incubation.